Confined vapor explosion in Kaohsiung City – A detailed analysis of the tragedy in the harbor city. (May 2016) - Yang, Hui-Ning; Chen, Jen-How; Chiu, Home-Jo; Kao, Ting-Jia; Tsai, Hsiao-Yun; Chen, Jenq-Renn
Abstract: On the midnight of July 31st, 2014, a catastrophic vapor explosion occurred in the downtown of Kaohsiung city. The incident was initiated from a leak of an underground pipeline transporting pressurized propylene liquid. Analysis of pipeline operation logs and pipeline break release modeling suggested that at least 90, 000 kg of propylene leaked, entered the underground trench and spread into the trench 4.5 km in distance before meeting an ignition source some three hours later after the leak. The ignition caused a significant confined vapor explosion which blew out the road above the underground trench, damaged more than one hundred vehicles on the road with thirty two fatalities and more than three hundred injuries. This article will first describe the background of the pipeline installation follows by an in-depth look at the explosion incident covering the events leading to the explosion, explosion damage, cause of the leak, spread of the leak, identification of a probable ignition source, and root causes in safety culture. Finally, lessons learnt and recommendations are given to prevent and mitigate the occurrence of similar incidents. Highlights: The catastrophic vapor explosion occurred in the downtown of Kaohsiung City on the midnight of July 31st, 2014 are analysed. Pipeline break release modeling showed that at least 90, 000 kg of propylene leaked. Detailed analyses were done on the events, identification of a probable ignition source, and root causes in safety culture. Lessons learnt and recommendations are given.